A synergetic strategy based on texture and Nano-TiO2 grease to improve the tribological and insulating properties of the matrix under current-carrying friction. (May 2023) - Yang, Kuo; Feng, Xin; Xia, Yanqiu
Abstract: Herein, a series of textures with different dimensions have been prepared on the copper surface by laser surface texture (LST). Micron-TiO2 and Nano-TiO2 grease were prepared by using TiO2 as an additive. Moreover, the tribological and insulating performances of the texture under TiO2 lubrication were investigated in detail. Results demonstrated that under Nano-TiO2 lubrication, the texture with appropriate dimple diameter has better tribological and insulating properties than non-texture Micron-TiO2 lubricant. Especially when the additive concentration is 1 wt%, Nano-TiO2 has the best anti-friction and anti-wear performance and enormous contact resistance. Characterization and analysis of the worn surfaces suggest that the synergistic effect of Nano-TiO2 and texture contributed to these excellent tribological and insulation properties.